Surveillance and Control of African Swine Fever in the Early Phase of the COVID-19 Pandemic, March-May 2020: A Multi-Country E-Survey - Desvars-Larrive, Amélie; Käsbohrer, Annemarie (Frontiers in Veterinary Science, 2022)
Stringent COVID-19 public health and social measures (PHSMs) have challenged the work of animal health professionals, especially in the early phase of the pandemic. We aimed to qualitatively describe how COVID-19 PHSMs have affected the surveillance and control of African swine fever (ASF) in Europe, assess how professionals engaged in these activities perceived the impact of the COVID-19 crisis, and identify potential areas of improvement. An online questionnaire was proposed via email between 9 December 2020 and 22 January 2021 to professionals engaged in ASF-related activities in Europe and Eastern neighboring countries. The questionnaire contained questions pertaining to ASF surveillance and control activities between March and May 2020, respondent´s perception of the impact of COVID-19 PHSMs on these activities, and respondent´s opinion on potential improvements to prepare future crises. Economic and sanitary variables were used to describe the national contexts over the study period. Twenty-seven respondents from 24 countries participated to the study. Essential activities related to surveillance and management of ASF were reduced and/or adapted but maintained in most surveyed countries. Communication was mentioned as the first area of improvement during crisis while maintenance of efficient veterinary services and surveillance activities were cited second and third top priorities. The need for the development of remote procedures was also recognized. Some respondents highlighted difficulties in ensuring biosecurity and biosafety of the field actors due to shortage in protective equipment. Only a small majority (52%) of the survey participants agreed that their institution/working group is better prepared to future lockdown-type situations. Our study emphasizes that short-term measures were globally successful to tackle the immediate impacts of the COVID-19 crisis on the routine duties of professionals involved in ASF surveillance and control. Our findings suggest that country-specific improvements are necessary to support and advance the preparedness of the actors involved in infectious animal disease surveillance and control in case lockdown-like measures are implemented. Overall, our results highlight the crucial importance of recognizing animal health services as essential activities during crisis.